Conflict between the Greater Rhea and humans in agricultural landscapes: implications for conservation of the last large herbivore of the southern Pampas - Pedrana, Julieta (2015)
South-eastern South America (SESA) hosts populations of a number of large herbivores, such as the Greater Rhea (Rhea americana). However, the natural grasslands of SESA have been subject to major transformation through agricultural development, primarily grazing, cropping and afforestation. Here, we assess the relative effects of environmental and anthropogenic predictors on the distribution of Greater Rheas in the southern Pampas at different spatial scales, and produce distributions maps of the species derived from habitat-suitability models. We undertook vehicle surveys in the southern Pampas over 2 years, surveying 4600 km of road each year, and recording a total of 146 sightings of 1353 individual Rheas. Generalised additive models were used to model the presence—absence of Greater Rheas in 250-m2 cells. The habitat suitability models suggest that preferred habitats included areas of high elevation supporting waterbodies and landscapes of grazing fields and native habitats, whereas centres of human activity negative affect the distribution of the species.